Molecular dynamics identifies semi-rigid domains in the PD-1 checkpoint receptor bound to its natural ligand PD-L1 - Kenn, Michael; Karch, Rudolf; Tomasiak, Lisa; Cibena, Michael; Pfeiler, Georg; Koelbl, Heinz; Schreiner, Wolfgang (Frontiers in Bioengineering and Biotechnology, 2022)
Leucocytes normally detect and kill any foreign organism invading the body. Sometimes, however, they erroneously attack vital cells of the own body. Such unwanted, autoimmune reactions are guarded against via checkpoints such as PD-1, the programmed cell death receptor 1. Each leucocyte carries PD-1 molecules (receptors) on its surface, capable to send their own leucocyte to death if activated by the appropriate (‘natural’) ligand, PD-L1. Cells in danger of being erroneously attacked, express PD-L1 on their surface. These activate PD-1 on attacking leucocytes and send them to death, thus curbing erroneous, autoimmune attack. Unfortunately, cancer cells exploit this mechanism: By expressing PD-L1, they guard themselves against leucocyte attack and thereby evade immune clearance. Checkpoint inhibitors are drugs designed to block the binding of PD-L1 to PD-1 receptors, and thereby re-enable immune reactions eliminating cancer cells. We explore pembrolizumab, a drug designed to bind to PD-1, without activating it. It binds competitively with PD-L1, should the latter be expressed by a cancer cell. As a consequence, PD-L1 cannot activate PD-1 anymore which frees the way for appropriate immune attack. We use three 600 ns all-atom molecular dynamics simulations to scrutinize molecular motions of PD 1 with its binding partner, the natural ligand PD-L1. Usually, atomic motion patterns are evaluated against whole molecules as a reference, disregarding that such a reference is a dynamic entity by itself, thus degrading stability of the reference. We rather identify semi-rigid domains, lending themselves as more stable and reliable reference frames against which even minute differences in molecular motion can be quantified precisely. We propose an unsupervised three-step procedure and demonstrate the results. In previous work of our group and others, minute differences in motion patterns proved decisive for differences in function. Here, several highly reliable frames of reference are established for future investigation of molecular mechanisms underlying binding ‘with activation’ of PD-1 (natural ligand) versus ‘binding without activation’ (any checkpoint inhibitor), based on molecular motion.